2021
DOI: 10.3724/sp.j.0254-6124.2021.0205
|View full text |Cite
|
Sign up to set email alerts
|

Local Time Differences in the Ionospheric Electromagnetic Ion Cyclotron Waves during Storm Time

Abstract: By using high-resolution (50 Hz) magnetic field observations from Swarm constellation, the temporal and spatial characteristics of Electromagnetic Ion Cyclotron (EMIC) waves in different local time sectors at mid-latitudes are investigated during the magnetic storm period of 16−25 March 2015. There are comparable number of EMIC wave events in the dawn and dusk sectors, while there are more EMIC wave events in the pre-noon sector than in the pre-midnight sector. The duskside preference is related to the plasmas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The SYISR Ne data are available at https://doi. org/10.17605/OSF.IO/4H5J8 (Sun, 2023). GOLD data presented in this research can be accessed at the GOLD Science Data Center (http://gold.cs.ucf.edu/search/).…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…The SYISR Ne data are available at https://doi. org/10.17605/OSF.IO/4H5J8 (Sun, 2023). GOLD data presented in this research can be accessed at the GOLD Science Data Center (http://gold.cs.ucf.edu/search/).…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Sun et al. (2021) also found that EMIC wave frequency is higher in the dawn to pre‐noon sector than that of the dusk to pre‐midnight sector and proposed that locations of the source region and concentrations of heavy ions may be different according to local time. Previous studies have speculated about possible causes of EMIC wave frequency variations at different MLT regions.…”
Section: Introductionmentioning
confidence: 99%